Assessments of Otolaryngology Resident Operative Experiences Using Mobile Technology: A Pilot Study. (13th August 2019) - Chen, Jenny X.; Kozin, Elliott; Bohnen, Jordan; George, Brian; Deschler, Daniel G.; Emerick, Kevin; Gray, Stacey T.
Abstract : Objectives: Surgical education has shifted from the Halstedian model of "see one, do one, teach one" to a competency‐based model of training. Otolaryngology residency programs can benefit from a fast and simple system to assess residents' surgical skills. In this quality initiative, we hypothesize that a novel smartphone application called System for Improving and Measuring Procedural Learning (SIMPL) could be applied in an otolaryngology residency to facilitate the assessment of resident operative experiences. Methods: The Plan Do Study Act method of quality improvement was used. After researching tools of surgical assessment and trialing SIMPL in a resident‐attending pair, we piloted SIMPL across an otolaryngology residency program. Faculty and residents were trained to use SIMPL to rate resident operative performance and autonomy with a previously validated Zwisch Scale. Results: Residents (n = 23) and faculty (n = 17) were trained to use SIMPL using a standardized curriculum. A total of 833 assessments were completed from December 1, 2017, to June 30, 2018. Attendings completed a median 20 assessments, and residents completed a median 14 self‐assessments. All evaluations were resident initiated, and attendings had a 78% median response rate. Evaluations took residents a median 22 seconds to complete; 126 unique procedures were logged, representing all 14 key indicator cases for otolaryngology. Discussion: This is the first residency‐wide application of a mobile platform to track the operative experiences of otolaryngology residents. Implications for Practice: We adapted and implemented a novel assessment tool in a large otolaryngology program. Future multicenter studies will benchmark resident operative experiences nationwide.